Dispersive characteristics of surface plasmon polaritons on negative refractive index gratings - Cuevas, Mauro (2011)
The dispersive characteristics of surface plasmon polaritons (SPPs) supported by a periodically corrugated boundary between vacuum and a negative refractive index, isotropic material were studied theoretically by numerical solution of a dispersion equation. SPP dispersion curves were correlated with the optical response of the corrugated boundary in frequency regions where SPPs can be excited by a normally incident plane wave. Abrupt reflectivity variations, characterized by the presence of a near unity maximum and an almost zero minimum, were found in regions where the boundary without corrugation exhibits low reflectivity and rather featureless reflectivity curves. © 2011 Elsevier B.V. All rights reserved.